Contextual constraints and the relevance discovery process: challenges facing knowledge gatekeepers in emerging economies. Issue 219 (22nd November 2016) - Kuznetsov, Andrei; Kuznetsova, Olga
Abstract: This paper explores conceptually the process of relevance discovery prompted by a major alteration in the institutional settings that has caused a radical change in the existing management knowledge paradigm, as new, mostly "imported", knowledge replaces the "old" knowledge base. This situation puts significant pressure on a particular group of experts designated in the literature as "knowledge gatekeepers". Their role is particularly important when external information requires contextual interpretation in order to be considered useful by other members of the social group. The paper focuses on recontextualisation as a critical element of relevance discovery and the transformation of "imported" knowledge from irrelevant to relevant and analyses the factors that influence the ability of knowledge gatekeepers to cope with the task of contextualisation. An account of two field studies of post‐communist marketisation is used to illustrate the challenges of contextualisation.